Quality Improvement through NABH Accreditation: A Review of Strategies for Preventing Medication Errors in Hospitals - Jamil, Mazhar; Rehan, Md; Khan, Abdullah; Asjad, Mohd; Siddiqui, Mohd Aftab; Salman, Mohd Tariq (Journal of Pharmacy Practice and Community Medicine, 2026)
Quality Improvement (QI) is a systematic approach aimed at enhancing the performance of healthcare organizations by improving patient safety, service quality, and overall satisfaction. In India, hospital quality is assessed using established frameworks, particularly those developed by the National Accreditation Board for Hospitals and Healthcare Providers (NABH) under the Quality Council of India (QCI). In 2018, the National Health Authority introduced quality certification requirements under the Ayushman Bharat Pradhan Mantri Jan Arogya Yojana (AB-PMJAY) to further strengthen healthcare standards and patient outcomes. This review highlights the role of NABH accreditation in improving healthcare quality and reducing medication errors through standardized protocols, continuous monitoring, and performance indicators. Additionally, the integration of Information Technology (IT) in healthcare systems can significantly minimize medication errors by enhancing communication, improving access to clinical information, and enabling real-time monitoring and decision support.
Keywords: Accreditation; Medication Errors; NABH; Patient Safety; Quality Improvement